2008
DOI: 10.1021/jp804030m
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Self-Assembly of Sm2O3 Nanoparticles into Nanorods: Simple and Large Scale Synthesis using Bulk Sm2O3 Powders

Abstract: Monodisperse samaria nanospheres and nanorods have been synthesized from commercial bulk Sm2O3 powders and various capping long-chain alkyl acids (e.g., oleic acid, myristic acid, decanoic acid). The synthesized materials were characterized by X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy (XPS), Fourier transform IR, thermogravimetric analysis, and N2 adsorption/desorption isotherms was employed to characterize these materials. The results revealed that the synthesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
119
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(127 citation statements)
references
References 67 publications
8
119
0
Order By: Relevance
“…For Sm 2 O 3 , a broad peak at 3400 cm -1 was due to H 2 O (or hydrated) adsorbed on the oxide surface. The peaks at 1412 and 1473 cm -1 were commonly observed and attributed to symmetric and asymmetric stretching of COO -, respectively [15]. Figure 5 displays the diffuse reflectance UV-Vis-NIR absorption spectra of Sm(OH) 3 Although the intensities were different before and after thermal annealing all the UV-Vis-NIR absorption peaks were in good match with the electronic transitions of Sm(III) [19,33].The absorption spectra between 900 and 2000 nm correspond to the f-f transitions from the ground state of 6 H 5/2 to 6 F 1/2,3/2,5/2,7/2,9/2,11/2 and 6 H 15/2 energy levels as assigned on the corresponding peaks [33].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Sm 2 O 3 , a broad peak at 3400 cm -1 was due to H 2 O (or hydrated) adsorbed on the oxide surface. The peaks at 1412 and 1473 cm -1 were commonly observed and attributed to symmetric and asymmetric stretching of COO -, respectively [15]. Figure 5 displays the diffuse reflectance UV-Vis-NIR absorption spectra of Sm(OH) 3 Although the intensities were different before and after thermal annealing all the UV-Vis-NIR absorption peaks were in good match with the electronic transitions of Sm(III) [19,33].The absorption spectra between 900 and 2000 nm correspond to the f-f transitions from the ground state of 6 H 5/2 to 6 F 1/2,3/2,5/2,7/2,9/2,11/2 and 6 H 15/2 energy levels as assigned on the corresponding peaks [33].…”
Section: Methodsmentioning
confidence: 99%
“…Sm(OH) 3 has also been prepared since Sm 2 O 3 could be obtained by a post-thermal dehydration [11,12]. Facial solution-based synthetic methods include hydrothermal [13][14][15], precipitation [11,16], solgel [18], and template [19] methods. Many different morphologies have been synthesized and reported, including nanorods [11,[15][16][17]20], nanodisks [18], nanowires [21,22], submicrospindles [23], nanoparticles [24], and nanoplates [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 14d, the O 1s core-level spectrum is characterized by the main peak at 531.18 eV, assigned to the oxygen of Sm(III)-O groups, 27 this indicates that the Sm(III) in the film could be in the form of oxides (Sm 2 O 3 ).…”
mentioning
confidence: 87%
“…14c). The two prominent peaks at 1083.18 eV and 1110.38 eV correspond to Sm(III), 27,28 whereas the weak peak pair at about 1090 and 1119 eV is ascribed to Sm(II). 29 The presence of Sm(II) in the coating coincides with the formation mechanism of the samarium film previously proposed, in which includes the reduction of Sm(III) to Sm(II).…”
mentioning
confidence: 99%
“…Only a few studies have been reported on the synthesis of samarium oxide nanoparticles or nanorods using thermal composition [13] or hydrothermal synthesis [14]. Fabrication of metal nanostructures by the template deposition method, pioneered by Martin [15,16], is one of the important processes.…”
Section: Introductionmentioning
confidence: 99%